Corporate Governance, Idiosyncratic Risk, and Information Flow - FERREIRA, MIGUEL A.; LAUX, PAUL A. (Journal of Finance, 2007)
ABSTRACT We study the relationship of corporate governance policy and idiosyncratic risk. Firms with fewer antitakeover provisions display higher levels of idiosyncratic risk, trading activity, private information flow, and information about future earnings in stock prices. Trading interest by institutions, especially those active in merger arbitrage, strengthens the relationship of governance to idiosyncratic risk. Our results indicate that openness to the market for corporate control leads to more informative stock prices by encouraging collection of and trading on private information. Consistent with an information‐flow interpretation, the component of volatility unrelated to governance is associated with the efficiency of corporate investment.